Ability of postoperative delirium to predict intermediate-term postoperative cognitive function in patients undergoing elective surgery at an academic medical centre: protocol for a prospective cohort study. Issue 3 (17th March 2018) - Aranake-Chrisinger, Amrita; Cheng, Jenny Zhao; Muench, Maxwell R; Tang, Rose; Mickle, Angela; Maybrier, Hannah; Lin, Nan; Wildes, Troy; Lenze, Eric; Avidan, Michael Simon
Abstract : Introduction: Postoperative delirium (POD) is a common complication in elderly patients, characterised by a fluctuating course of altered consciousness, disordered thinking and inattention. Preliminary research has linked POD with persistent cognitive impairment and decreased quality of life. However, these findings maybe confounded by patient comorbidities, postoperative complications and frailty. Our objective is to determine whether POD is an independent risk factor for persistent impairments in attention and executive function after elective surgery. Our central hypothesis is that patients with POD are more likely to have declines in cognition and quality of life 1 year after surgery compared with patients without POD. We aim to clarify whether these associations are independent of potentially confounding factors. We will also explore the association between POD and incident dementia. Methods and analysis: This study will recruit 200 patients from the ongoing Electroencephalography Guidance of Anesthesia to Alleviate Geriatric Syndromes (ENGAGES) study. Patients who live ≤45 miles from the study centre or have a planned visit to the centre 10–16 months postoperatively will be eligible. Patients with POD, measured by the Confusion Assessment Method, will be compared with patients without delirium. The primary outcome of cognitive function and secondary outcomes of quality of life and incident dementia will be compared between cohorts. Cognition will be measured by Trails A and B and Stroop Color and Word Test, quality of life with Veteran's RAND 12-item Health Survey and incident dementia with the Short Blessed Test. Multivariable regression analyses and a Cox proportional hazards analysis will be performed. All results will be reported with 95% CIs and α=0.05. Ethics and dissemination: The study has been approved by the Washington University in St. Louis Institutional Review Board (IRB no 201601099). Plans for dissemination include scientific publications and presentations at scientific conferences. Trial registration number: NCT02241655 .